A Critical Discourse Analysis: The Depiction of Pancasila Principles in English for Nusantara Textbook - Niqita Pradilaf, Geby; Basya, Dihliza; Ghozali, Imam (Linguapedia, 2025)
The Pancasila student profile as part of the independent curriculum is one of the government’s efforts to spread the values and practices of Pancasila in all learning domains, both in the teaching and learning process and in the textbooks used and recently approved by the government. The purpose of this study was to enhance public consciousness, particularly among education policymakers, teachers, and students, regarding the crucial role of textbooks in upholding Pancasila values and equipping students with the necessary wisdom to navigate the future in alignment with the values imparted through textbooks. This research specifically examines the values of Pancasila, namely 1) faith, devotion to God almighty, and noble morals, 2) independence, 3) Gotong Royong, 4) global diversity, 5) critical reasoning, and 6) creativity, in accordance with Minister of Education and Culture regulation Number 22 of 2020 concerning the Strategic plan of the Ministry of Education and Culture for 2020-2024. Efforts to maintain The Pancasila values contained in English for Nusantara textbook published by The Ministry of Education and Culture for Grade 7th Junior School students. The research employs the English for Nusantara Textbook for 7th grade Junior High School as the instrument. The critical discourse analysis approach is utilized to examine the ideological values conveyed in the textbook’s messages, both explicitly and implicitly, within their respective contexts.